2012
DOI: 10.1017/s1751731111001169
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters and environmental effects on temperament score and reproductive traits of Nellore cattle

Abstract: Animal temperament is a trait of economic relevance and its use as a selection criterion requires the identification of environmental factors that influence this trait, as well as the estimation of its genetic variability and interrelationship with other traits. The objectives of this study were to evaluate the effect of the covariates dam age at calving (ADC), long yearling age (YA) and long yearling weight (YW) on temperament score (T) and to estimate genetic parameters for T, scrotal circumference (SC) at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
23
1
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 14 publications
10
23
1
7
Order By: Relevance
“…The values estimated for genetic variance (3.602, Table 3) and heritability (0.52 ± 0.019, Table 3) for SC, as usually described in literature (e.g. Barrozo et al, 2012), indicate the possibility of good responses when selection is applied to this trait. Weak genetic correlations were estimated between female reproductive traits and SC; therefore, no effective genetic response in those traits through SC selection is expected.…”
Section: Resultsmentioning
confidence: 70%
“…The values estimated for genetic variance (3.602, Table 3) and heritability (0.52 ± 0.019, Table 3) for SC, as usually described in literature (e.g. Barrozo et al, 2012), indicate the possibility of good responses when selection is applied to this trait. Weak genetic correlations were estimated between female reproductive traits and SC; therefore, no effective genetic response in those traits through SC selection is expected.…”
Section: Resultsmentioning
confidence: 70%
“…Una característica que puede ser usada como criterio de selección de los machos con el objetivo de aumentar la fertilidad de los rebaños, es la circunferencia escrotal (CE). Este parámetro presenta una estimativa de heredabilidad de moderada a alta (Barrozo et al, 2012), es de fácil medición y presenta correlación genética favorable con la tasa reproductiva de las hembras (Mello, 2014). El peso testicular está en función directa con la cantidad de epitelio seminífero productor de esperma y por lo tanto, con la concentración espermática del eyaculado.…”
Section: Introductionunclassified
“…This evaluation was carried out following the procedure described by Barrozo et al (2012), such that the animals had their temperament classified according to:…”
Section: Animals and Datamentioning
confidence: 99%
“…Therefore, it is necessary to use appropriate statistical models to correctly evaluate this trait in animal breeding programs that adopt temperament as a selection criterion. Several studies have reported heritability estimates for temperament scores in cattle ranging from 0.13 to 0.40 (Burrow, 2001;Kadel et al, 2006;Barrozo et al, 2012); linear models were used in most of these studies to estimate the genetic parameters. However, given the categorical nature of temperament scores and their asymmetric distribution, it is possible that some assumptions, such as the normality and homoscedasticity of residuals, would not be met when analyzing this trait using linear models.…”
Section: Introductionmentioning
confidence: 99%